Iaiá Garcia - Machado de Assis, 1839-1908 (Studies in Romance languages (Lexington, Ky.), 2015)
The last of four novels that preceded Machado de Assis's famous trilogy of realistic masterpieces, Iaiá Garcia belongs to what critics have called the Brazilian author's ""romantic"" phase. But it is far more than that implies. Like his other early works, Iaiá Garcia foreshadows the themes and characters of Assis's most masterful novels. Iaiá Garcia intertwines the lives of three characters in a subtly and wryly developing relationship. While the youthful Iaiá is growing into womanhood, a tentative love affair occurs between the aristocratic Jorge and the prideful Estela. This affair is affl.